Study of thrombopoietin levels in some Egyptian patients with chronic liver diseases secondary to the hepatitis C virus - Enayat O. Ezzat; Somayh E. Suliman; Samiha Abo El-Yazeed; Fatma M. Ahmad; Sahar K. Said (SpringerOpen, 2012)
IntroductionThe hepatitis C virus (HCV) is a leading cause of chronic liver disease (CLD), cirrhosis, and hepatocellular carcinoma, as well as the most common indication for liver transplantation in many countries. PurposeThis work was carried out to study of thrombopoietin (TPO) level in Egyptian patients with chronic hepatitis C and liver cirrhosis with HCV. Patients and methods This work was conducted on 40 patients proved to have chronic liver disease due to chronic HCV infection by positive HCV antibody by enzyme-linked immunosorbent assay, PCR for HCV RNA, abdominal ultrasonography, and histopathological examination. Twenty of these patients had chronic active hepatitis C (CAH) and the other 20 patietns had liver cirrhosis. Fifteen apparently healthy individuals (negative for HCV antibody) were included in a control group. None of the patients had received interferon therapy. Patients with other causes of CLD, chronic renal disease, diabetes, endocrinal hematological, and other debilitating diseases were excluded. All the patients studied were subjected to the following: complete medical history, full clinical examination, laboratory investigations including complete blood picture, liver function tests, fasting blood sugar, 2 h postprandial, HCV antibody and PCR for RNA of HCV; serum TPO level, abdominal ultrasonography, and liver biopsy for histopathological examination. Results Our Results showed a highly significant reduction in the platelet count in patients with CAH (192.55±41.02) and cirrhotic patients (159.800±86.189) in comparison with (322.67±38.12) the control group (P<0.01). There was nonsignificant increase in TPO in patients with CAH (115.93±71.66) and a significant decrease in TPO in cirrhotic patients (77.504±64.576) in comparison with (107.98±52.53) the control group. In the cirrhotic patients, there was a significant positive correlation between TPO and platelet count, whereas there was no correlation between TPO level and liver enzymes (alanine aminotransferase and aspartate aminotransferase) in all patients. In addition, a significant decrease in TPO was found in cirrhotic patients in comparison with CAH patients. Conclusion Serum TPO level was elevated in patients with chronic viral C hepatitis as a compensatory response to the reduction of platelet count with still functionally active liver cells, but as the disease progress to cirrhosis which also is associated with thrombocytopenia, TPO production is impaired, with failure to compensate the low platelet count aggravating thrombocytopenia.